The Relationship between Lifestyle and Stress Levels with the Incidence of Diabetes Mellitus: Literature Study - Ika Lilis Istiadah; Dwi Heppy Rochmawati; Erna Melastuti; Ahmad Ikhlasul Amal (Indonesian Journal of Global Health Research, 2025)
Diabetes Mellitus (DM) is a chronic disease marked by high blood glucose due to insulin dysfunction. Its prevalence is rising, with Indonesia ranking seventh globally. Unhealthy lifestyles and stress exacerbate the issue, highlighting the need for improved prevention and management strategies. This study examines how lifestyle and stress influence DM incidence in Indonesian patients, identifying risk factors to enhance healthcare strategies. A systematic review using PRISMA guidelines analyzed studies from various databases (2019-2024), selecting relevant articles based on inclusion criteria and extracting key research data. From 10 reviewed journals, 4 linked lifestyle to DM, 1 identified sedentary behavior as a prediabetes risk, and 5 highlighted stress as a major factor. Preventing and managing DM requires a healthy lifestyle, stress management, and healthcare interventions to enhance patient well-being while reducing economic and health burdens.